Successful Treatment with Vinblastine in a Patient with Relapsed Anaplastic Large Cell Lymphoma - SAKO, Masahiro; ISHII, Takefumi; NOMA, Haruyoshi; OSUGI, Yuko (The Japanese Journal of Pediatric Hematology, 2004)
The therapeutic results of pediatric anaplastic large cell lymphoma (ALCL) have been improved with the development of modern multi-agent chemotherapy. However, the best therapy for relapsed patients has not been clear. We report here a 5-year-old girl with ALCL (stage III) who was successfully treated with weekly vinblastine (VBL). At the first presentation she was treated with the short-pulse B-non Hodgkin's lymphoma-type chemotherapy and achieved complete remission. However, she had a relapse one month after the cessation of chemotherapy. She obtained the remission with the same induction chemotherapy as before and VBL. After that VBL was administered once a week as a maintenance therapy. Now she has been disease free for 24 months. The side effect of VBL was only transient mild fever after injection. Our case was successfully treated with a maintenance therapy of VBL without high-dose chemotherapy. Further studies are necessary to know the appropriate way to use VBL for ALCL.